2018
DOI: 10.1136/jech-2018-210438
|View full text |Cite
|
Sign up to set email alerts
|

Inequities in exposure to occupational risk factors between Māori and non-Māori workers in Aotearoa New Zealand

Abstract: This is one of the first studies internationally to compare occupational risk factors between indigenous and non-indigenous people. These findings suggest that the contribution of the occupational environment to health inequities between Māori and non-Māori has been underestimated and that work tasks may be unequally distributed according to ethnicity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 26 publications
1
17
0
Order By: Relevance
“…To our knowledge, no other studies have examined the prevalence of exposure to occupational carcinogens among New Zealand-born workers in Australia. However, studies conducted in New Zealand have found that Māori workers are more likely than non-Māori workers to be exposed to dusts and smoke at work, 8,9 in line with our findings.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…To our knowledge, no other studies have examined the prevalence of exposure to occupational carcinogens among New Zealand-born workers in Australia. However, studies conducted in New Zealand have found that Māori workers are more likely than non-Māori workers to be exposed to dusts and smoke at work, 8,9 in line with our findings.…”
Section: Discussionsupporting
confidence: 92%
“…We did not find any difference between Māori/Pasifika and New Zealand Caucasians working in Australia in terms of job vulnerability, job strain, and job insecurity. In New Zealand, past research has found Māori women to be more likely to experience high work stress than non-Māori women, 8,9 although another study found no differences between workers of Māori and European ethnicity in terms of psychological work strain. 28 Other research in New Zealand has found Māori workers to report lower job security than those of European ethnicity.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…Māori health inequities are well documented (Blakely et al 2005;Robson and Harris 2007;Signal et al 2007;Hill et al 2013;Anderson et al 2016;Metcalfe et al 2018;Reid, Cormack, et al 2018). The ongoing impacts of colonisation, racism, migration and marginalisation in maintaining these inequities are also well documented (Reid and Robson 2000;Blakely et al 2011;Bécares et al 2013;Came 2014;Reid et al 2014;Dew et al 2015;Harris et al 2015;Signal et al 2015;Lawrenson et al 2016;Denison et al 2018;Huria et al 2018;Rahiri et al 2018;.…”
Section: Introductionmentioning
confidence: 99%